Juridical Review of Consumer Protection in Halal Assurance of Poultry: A Study on the Feasibility of Product Consumption - May Shinta Retnowati; Daud Sukoco; Musta’an Al Faruqi (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
The current halal product guarantee can undeniably be realized through regulatory efforts on product assurance that are positively initiated by the government. With the guarantee of halal products, people, both Muslims and non-Muslims, can consume safely. In Law Number 33 of 2014 concerning Halal Product Guarantee, the law requires Poultry Slaughterhouses (RPU) to have halal certificates but the phenomenon in the community is that there are still many Poultry Slaughterhouses (RPU) that do not have halal certificates to ensure the feasibility of the products produced, such as halal product guarantees.The purpose of this study is to explain the juridical review of consumer protection guarantees from products that have not been certified halal. This research method uses a type of field research (qualitative) with a juridical approach that is analyzed descriptively. The results of this study show that there are still many meat sellers (buthcer) and RPUs do not have halal certification. This is a serious problem to ensure the circulation of meat, although there have been many rules stipulated to ensure halal and product feasibility, there are still many products in the field that have not been certified halal meat. The presence of the Head of BPJPH Decree No. 77 of 2023 is a solution for RPU to carry out halal certification immediately to ensure the halalness of their products, but the obstacle of RPU is the high cost of its submission, so it is hoped that the government can provide a halal certification subsidy program for RPU such as the self-declare program.